Loss of overproduction of polypeptide release factor 3 influences expression of the tryptophanase operon of Escherichia coli. - Yanofsky, C (1996)
Expression of the tryptophanase (tna) operon of Escherichia coli is regulated by catabolite repression and by tryptophan-induced inhibition of Rho-mediated transcription termination. Previous studies indicated that tryptophan induction might involve leader peptide inhibition of ribosome release at the stop codon of tnaC, the coding region for the operon-specified leader peptide. In this study we examined tna operon expression in strains in which the structural gene for protein release factor 3, prfC, is either disrupted or overexpressed. We find that prfC inactivation leads to a two- to threefold increase in basal expression of the tna operon and a slight increase in induced expression. Overexpression of prfC has the opposite effect and reduces both basal and induced expression. These effects occur in the presence of glucose and cyclic AMP, and thus Rho-dependent termination rather than catabolite repression appears to be the event influenced by the prfC alterations. prfC inactivation also leads to an increase in basal tna operon expression in various rho and rpoB mutants but not in a particular rho mutant in which the basal level of expression is very high. The effect of prfC inactivation was examined in a variety of mutants with alterations in the tna leader region. Our results suggest that translation of tnaC is essential for the prfC effect. The tryptophan residue specified by tnaC codon 12, which is essential for induction, when replaced by another amino) acid, allows the prfC effect. Introducing UAG or UAA stop codons rather than the normal tnaC UGA stop codon, in a strain with an inactive prfC gene, also leads to an increase in the basal level of expression. Addition of the drug bicyclomycin increases basal operon expression of all mutant strains except a strain with a tnaC'-'lacZ fusion. Expression in the latter strain is unaffected by prfC alterations. Our findings are consistent with the interpretation that ribosome release at the tnaC stop codon can influence tna operon expression.